Grief is the thing with feathers - Porter, Max (Graywolf, 2016)
In a London flat, two young boys face the unbearable sadness of their mother's sudden death. Their father, a Ted Hughes scholar and scruffy romantic, imagines a future of well-meaning visitors and emptiness. In this moment of despair they are visited by Crow-- antagonist, trickster, healer, babysitter. This sentimental bird is drawn to the grieving family and threatens to stay until they no longer need him. As weeks turn to months and the pain of loss gives way to memories, the little unit of three starts to heal. In this extraordinary debut-- part novella, part polyphonic fable, part essay on grief-- Max Porter's compassion and bravura style combine to dazzling effect. Full of unexpected humour and profound emotional truth, 'Grief Is the Thing with Feathers' marks the arrival of a thrilling new talent.--